WARGA BANTU WARGA: MODAL SOSIAL SEBAGAI INSTRUMEN NON GOVERMENT YANG MEMPERKUAT PEMERINTAHAN DESA DI SIGI KELUAR DARI KRISIS - Muthia; Sitti Rabiatul Wahdaniyah; Sunardi (Musawa: Journal for Gender Studies, 2024)
This article will examine how social capital in rural areas, manifested through the citizen-help-citizen movement, has contributed to residents and village governments overcoming the crisis problems caused by the pandemic. There are two movements of citizens helping residents: the women's network at the neighborhood level and the roa guard roa movement. This research took place in rural Sigi, Central Sulawesi. Data collection was carried out through interviews using fieldwork. We frame these findings through the lens of Non-Governmental Innovation with a starting point in the social capital of citizens. We argue that non-governmental innovation has created natural disaster management. The experience of residents going from one disaster condition to another produces collective navigation for residents. They finally have some knowledge tools that can be used when facing a crisis, such as knowing what to do and how to do it. This knowledge tool helps governments at the village level in minimizing the risk of crisis due to disasters.